MOTIVASI INDONESIA MENYEPAKATI PENETAPAN BATAS MARITIM TERKAIT ZONA EKONOMI EKSKLUSIF DENGAN FILIPINA - Ika Nurasma Yanti; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to understand why are Indonesia want to aggreed about maritime boundary delimitation that connected Exclusife Economic Zone with Filipina on May 2014 that assigned in Manila. Also explain how eforts Indonesia and Filipina to agreed about boundary delimitation (EEZ) that location is North Sulawesi (Indonesia) and Mindanao (Filipina) so there is occur joint overlapping that caused Economic Exclusife Zone can not reach 200 mil. Last thing to be discussed about what the motivation of Indonesia to agreed about Economic Exclusife Zone with Filipina, Indonesia want to agreed with this cooporation because there is national interest such as economic,security and politic.This research theoretically has built with neorealism perspectives on International Relations and supported by International Cooperation, and International Security theories and national interest. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internets that has related to the problems.In this research, the motivation of Indonesia to agreed about boundary delimitation (EEZ) with Filipina can be the first step to increase the bilateral relation between two countries and can be example to others countries that have a same case so can solve this problem liked Indonesia and Filipina.Keywords : Economi Exclusife Zone, Indonesia, Philippines, Security, Cooperatian